1987
DOI: 10.3109/13880208709060910
|View full text |Cite
|
Sign up to set email alerts
|

Biological Assay ofCroton penduliflorusHutch. Seed Oil in Mice

Abstract: Croronpenduliflorus seed oil was obtained by successively extracting the dried seeds with petroleum ether (40"-60°). Graded doses of the extracted oil suspended in 5% Tween 20 were administered orally to groups of mice and the number of wet faeces (WF) produced at hourly basis for 9 hrs and at the end of 24 hrs were recorded. Linear dose-response relationships were obtained. A time-course of the purgative effect was established showing a maximum response between 9 and 24 hrs irrespective of the dose. An acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1990
1990

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Other organs which were affected with the heart, testis, spleen and kidney to a lesser extent (only at 800 mg/kg). These doses were, however, much higher than the therapeutic dose of Cl' seed oil because 600mg/kg of the oil is the dose which produces 50% mortality in a mouse population (Asuzu, 1987). The severe effect of CP seed oil in the liver could be due to the phenomenon of 'first pass effect', which means that substances absorbed from the gut pass first to the liver via the portal vessels.…”
Section: Histopathologymentioning
confidence: 98%
See 1 more Smart Citation
“…Other organs which were affected with the heart, testis, spleen and kidney to a lesser extent (only at 800 mg/kg). These doses were, however, much higher than the therapeutic dose of Cl' seed oil because 600mg/kg of the oil is the dose which produces 50% mortality in a mouse population (Asuzu, 1987). The severe effect of CP seed oil in the liver could be due to the phenomenon of 'first pass effect', which means that substances absorbed from the gut pass first to the liver via the portal vessels.…”
Section: Histopathologymentioning
confidence: 98%
“…In a study on the purgative effect of CP oil in mice, the maximum cumulative number of wet faeces was observed between the 9th and 24th hours (Asuzu, 1987). It is important to mention that though mice dosed orally with 180-300mg/kg of CP oil in a previous study did not show any toxic signs, this study has revealed that some mild inflammatory effects were evident even at 250mg/kg, which is the effective dose in 50% of a mouse population (Asuzu, 1987).…”
Section: Figure 2 Focal Necrosis In the Liver (H And E ~80)mentioning
confidence: 99%